Group Triple P intervention effects on children and parents: a systematic review and meta-analysis - Nogueira, Sandra (2022)
Supporting parents through the delivery of evidence-based parenting interventions (EBPI) is a way of promoting children’s rights, given the known benefits to child development and family wellbeing. Group Triple P (GTP) is an EBPI suitable for parents of children aged 2–12 years, who experience parenting difficulties, and/or child behavior problems. Even though GTP has been intensively studied, information lacks on the magnitude of its effects, considering the risk of bias within and across prior research. To address this, a systematic review and meta-analysis (PROSPERO registration CRD42019085360) to evaluate the effects of GTP on child and parent outcomes at short- and longer-term was performed. Through a systematic search of a set of databases, 737 research papers were identified, and 11 trials were selected. The risk of bias within and across studies was evaluated. Significant positive effects of GTP were found immediately after the intervention for child behavior problems, dysfunctional parenting practices, parenting sense of competence, psychological adjustment, parental stress levels, conflict, and relationship quality. Six months after the intervention, positive effects were found only for child behavior problems. Data suggest that GTP might be an effective EBPI leading to positive family outcomes. Substantial risk of bias was found, highlighting the importance of improving the quality of research.